'Imagineering' mixed reality (MR) immersive experiences in the postdigital revolution: innovation, collectivity, participation and ethics in staging experiments as performances. Issue 2 (3rd July 2018) - Demetriou (Yiota), Panayiota A.
ABSTRACT: At the frontiers of our technoculture and experience economy, artist-researchers as catalytic agents become Imagineers and entrepreneurs of themselves. Arts are quantified in expectations of extending forms of communication with people and our environments, by creating humanistic ways of interfacing with machines. Within the experience economy the term 'immersion' is overused trending towards VR, which has troubled many researchers and practitioners across disciplines. Drawing on perspectives from performance studies, digital humanities, and human-computer interaction (HCI), this paper reviews the role of XR-enabling technologies, beyond VR, in designing immersive experiences, and their integration into performance practices. It discusses the shift of the artist's role in imagineering new resources and new ways of working to immerse audiences, and it evaluates this in a postdigital context. It discusses how immersion operates, and critiques components necessary to create affective environments in terms of audience engagement, agency, participation, involvement, presence, embodiment and interaction. The article discusses how performance as a lab can act as a method of inquiry by bringing the anthropological, performative and theatrical perspectives; and the ethics of to testing immersive-enabling technologies and/or experiences within the context of live performances.